Improved online hydrogen isotope analysis of halite aqueous inclusions. (4th March 2019) - Fourel, François; Lécuyer, Christophe; Seris, Magali; Blamey, Nigel; Brand, Uwe; Fralick, Philip; Volders, Filip
Abstract: We demonstrate an improved method based on continuous‐flow elemental analyser pyrolysis isotopic ratio mass spectrometry (CF‐EA‐PY‐IRMS) to measure the 2 H/ 1 H ratios of water trapped in halite crystals. Two challenges to overcome are the low hydrogen concentration of samples (10‐50 μmol H2 ·g −1 ) and the high chloride concentration released when reacting halite in an elemental analyser. We describe an optimization procedure for determining the 2 H/ 1 H ratio of this trapped water with an acceptable accuracy. This technique involves the use of a high‐temperature Cr reactor to quantitatively convert H2 O into H2 . The initial step was performed on halite crystals precipitated from a water reservoir where 2 H/ 1 H ratios were monitored from its initial stage until the end of evaporation. The 2 H/ 1 H isotopic analyses were automated online in continuous‐flow mode. Precision of the method was determined for those "synthetic" samples with hydrogen concentrations ranging from 0.2 to 0.5 wt%. 2 H/ 1 H isotopic ratios of evaporating waters bracket the compositions of water inclusions. The formation of fluid inclusions is not instantaneous and records the isotopic signature of the residual waters across a time range during which the isotopic values of the water still evolve. This property explains why the δ 2 HVSMOW standard deviation of ±5‰ (2σ) observed for 10‐mg aliquots of halite exceeds the instrumental error (about ±1.5‰ 2σ) determined on the basis of IAEA‐CH7, NBS 30, and NBS 22 references along with calibrated waters with and without added halite crystals. We also applied this method to Mesoproterozoic (1.4 Ga) and Neoproterozoic (0.8 Ga) halite samples with relatively low hydrogen concentrations (300‐1500 ppm). The measured δ 2 HVSMOW values for Precambrian waters range from −89‰ to −54‰. We propose that this technique offers a new perspective and great potential for palaeoenvironmental reconstructions based on the 2 H/ 1 H analyses of water trapped in halite.